Comparative macroanatomical study of the neurocranium in some carnivora - Karan, M; Timurkaan, S; Özdemir, D; Ünsaldi, E (Wiley, 2006)
This study was carried out to investigate the specific anatomical features of the neurocranium of the skull of the dog, cat, badger, marten and otter. Twenty-five animals (five from each species) were used without sexual distinction. The neurocranium consists of os occipitale, os sphenoidale, os pterygoideum, os ethmoidale, vomer, os temporale, os parietale and os frontale. The processus paracondylaris is projected ventrally in the cat, dog, marten and badger, and caudally in the otter. Two foramina were found laterally on each side of the protuberantia occipitalis externa in the otter, and one foramen was found near the protuberantia occipitalis externa in the badger. Foramen was not seen in other species. Paired ossa parietalia joined each other at the midline. forming the sutura sagittalis in the badger, dog, otter and cat while it was separated by the linea temporalis in the marten. The os frontale was small in otters, narrow and long in martens, and quite wide in cats and dogs. The bulla tympanica was rounded in the marten, dog, cat and badger; dorsoventral compressed in otter, and it was very large in all species examined. These observations represented interspecies differences in the neurocranium of marten, otter, badger. cat and dog.